Rural-urban disparity in induced abortion in Ghana: A multivariate non-linear decomposition analysis of the Ghana Maternal Health Survey - Isaac Yeboah; Martin Wiredu Agyekum; Jerry John Ouner; Duah Dwomoh; Desmond Klu; Mary Naana Essiaw; Andrew Kweku Conduah; Sarah Asaah Owusu-Kwankye (PLoS ONE, 2025)
Globally, 73.3 million induced abortions were recorded between 2015 and 2019. There are significant disparities in induced abortions across the rural-urban divide that necessitate targeted policies. In this study, we decomposed the rural-urban disparities in induced abortion in Ghana. Data for the study were extracted from the most recent 2017 Ghana Maternal Health Survey. The sample for this study consisted of women who had ever been pregnant, resulting in a weighted sample of 18,140. A multivariate non-linear decomposition model was employed to decompose the rural-urban disparities in induced abortion. The results were presented using coefficients and percentages. The proportion of women who have had induced abortions in their lifetime was 27.1%. Induced abortion was higher in urban areas (34.1%) than in rural areas (19.4%). Approximately 55 percent of the rural-urban disparities in induced abortion were attributable to differences in women’s socio-demographic and obstetric characteristics. Hence, if women’s socio-demographic and obstetric characteristics were equalled, the rural-urban disparity in induced abortion would be decreased. Region of residence (25.4%), education (16.6%), and parity (9.4%) explained approximately 51 percent of the rural-urban inequality in induced abortion. This study shows significant rural-urban disparities in induced abortion, with the disparities being attributable to the differences in socio-demographic and obstetrics characteristics: region of residence, education, and parity. Policymakers could focus and work on intensifying sexual and reproductive health educational messages, particularly, among women residing in the middle and southern ecological zone of Ghana, and also targeting the educated.